An asymptotic homogenization model for smart 3D grid-reinforced composite structures with generally orthotropic constituents - Hassan, Essmat M.; Kalamkarov, Alexander L.; Georgiades, Tasos (My University, 2009)
A comprehensive micromechanical model for smart 3D composite structures reinforced with a periodic grid of generally orthotropic cylindrical reinforcements that also exhibit piezoelectric behavior is developed. The original boundary value problem characterizing the piezothermoelastic behavior of these structures is decoupled into a set of three simpler unit cell problems dealing, separately, with the elastic, piezoelectric and thermal expansion characteristics of the smart composite. The technique used is that of asymptotic homogenization and the solution of the unit cell problems permits determination of the effective elastic, piezoelectric and thermal expansion coefficients. The general orthotropy of the constituent materials is very important from the practical viewpoint and makes the analysis much more complicated. Several examples of practical interest are used to illustrate the work including smart 3D composites with cubic and conical embedded grids as well as diagonally reinforced smart structures. It is also shown in this work that in the limiting particular case of 2D grid-reinforced structures with isotropic reinforcements our results converge to earlier published results.
Keywords: Reinforced thermoplastics; Cell membranes; Differential equations; Smart structures; Fits and tolerances; Models; Tolerance averaging